LUNG ABSCESS AND AIR-FLUID LEVEL - Chang, Chee Yik (Journal of Ayub Medical College Abbottabad, 2021)
A 49-year-old male, chronic smoker with a background of diabetes mellitus and hypertension presented with a one-month history of productive cough, reduced appetite, and weight loss. He reported no history of alcoholism, fever, breathlessness, haemoptysis, and chest pain. The chest radiograph showed a cavitating lung lesion with air-fluid level in the right upper lobe (figure-1). CT of the thorax later revealed a well-defined irregular thin-wall enhancing cavitating lesion with air-fluid level within (7.0Ã—6.5Ã—5.6 cm), seen at the apical segment of the right upper lobe, which was indicative of lung abscess (figure-2). There were no enlarged hilar or mediastinal lymph nodes. The workup for pulmonary tuberculosis and malignancy was negative. He was administered with intravenous amoxicillin-clavulanic acid 1.2 g every 8 hours. A repeat thoracic CT done at a 2-week interval did not show any radiological improvement. In view of poor response to antimicrobial therapy, CT-guided percutaneous catheter drainage was attempted but there was no output from the drain. The sputum culture yielded Klebsiella pneumoniae and Serratia marcescens, susceptible to piperacillin-tazobactam and cefuroxime. He received intravenous piperacillin-tazobactam for 2 weeks, followed by a prolonged course of oral cefuroxime for 3 months. The lung abscess completely resolved upon completion of antibiotic therapy.